The effects of three hamstring programmes on strength and sprinting performance in female footballers: A randomised controlled trial - Enda Whyte; Siobhán O’Connor; Aaron Connolly; Eve Hession; Jonathan Kennedy; Bernard O’Boyle; Joshua Thorp; Sam Timmons; Aoife Burke (PLoS ONE, 2026)
Objective Hamstring strain injuries (HSIs) frequently occur in female football, with sprinting being a common mechanism of injury. During sprinting, the considerable strength requirements of the knee flexors and hip extensors indicate their importance in performance and may partially explain the high incidence of HSIs. This study examined the effectiveness of 3 interventions on hip extensor and knee flexor strength and sprint performance in female footballers using a randomised controlled study design (ClinicalTrails.gov: NCT0573327). Methods Thirty-five healthy young female footballers (age = 20.9 ± 1.3 years, stature = 167.8 ± 5.4 cm, body mass = 66.8 ± 8.4 kg) from Dublin City University were randomized to Nordic hamstring exercise (NHE), single leg hamstring bridge (SLHB) or razor hamstring curl (RHC) interventions. A two-way repeated measures analysis of variance determined main effects of time (pre vs post), group (NHE vs SLHB vs RHC) and interaction effects on normally distributed peak torque variables of the dominant and non-dominant limbs (isometric knee flexor at 30° knee flexion, eccentric knee flexor during the NHE and isometric hip extensor at 0° and 30° hip flexion) and sprint variables (0-5m, 0-15m, 0-30m sprint times, maximal horizontal force production, theoretical velocity and horizontal power output). Non-normally distributed data (eccentric knee torque during the NHE) were investigated using Wilcoxon signed rank (time main effects) and Kruskal Wallis (group main effects) tests. Results No interaction or group effects were observed for strength measures ( p = 0.44–0.96, ɳ 2 =>0.01–0.05). There was a significant time effect for isometric knee flexor peak toque ( p < 0.001;ɳ 2 = 0.60–0.62) and knee flexor peak toque during NHE testing ( p = 0.008–0.014; r = 0.29–0.32), and isometric hip extensor peak torque at 0° ( p < 0.001;ɳ 2 = 0.59–0.58) and 30° ( p < 0.001–0.011;ɳ 2 = 0.19–0.32). No interaction or main effects for sprint variables ( p = 0.093–0.957, ɳ 2 =<0.01–0.09) were observed. Conclusion Participants in all 3 intervention groups demonstrated strength increases measurements after 4 weeks. Interventions of longer duration or different components should be considered for targeting improvements in sprint performance.